Neutrino Constraints and Detection Prospects from Gamma-Ray Bursts with Different Jet Compositions - Yang-Dong-Jun Ou; Hou-Jun Lü; Xue-Zhao Chang; Xiao-Xuan Liu; En-Wei Liang (The Astrophysical Journal)
The prompt emission mechanism of gamma-ray bursts (GRBs) is a long-standing open question, and GRBs have been considered as potential sources of high-energy neutrinos. Despite many years of search for the neutrino events associated with GRBs from IceCube, there were no results. However, the absence of search results for neutrinos provides a unique opportunity to constrain the parameter space of GRB jet models. In this paper, we chose four peculiar GRBs with two different types of jet composition to investigate neutrino emission. It is found that only GRB 211211A could be well constrained within the dissipative photosphere model. By adopting the specific parameters of the photosphere, one can obtain ε _p / ε _e < 8 for f _p > 0.2 from GRB 211211A. For the Internal-collision-induced Magnetic Reconnection and Turbulence (ICMART) model, we can effectively constrain neither GRB 230307A nor GRB 080916C. Moreover, we also investigate the detection prospects of high-energy neutrinos from GRBs and find that it is difficult to detect at least one high-energy neutrino associated with GRBs from the ICMART model even during the IceCube-Gen2 operation. For the GRB 211211A-like events, it is possible to detect at least one neutrino coincident with the gravitational wave during the IceCube-Gen2 operation, if such an event originated from mergers of compact stars within the photosphere dissipation.